INFLUENCE OF THE TELEVISION PROGRAM "AULA365" IN THE LEARNING OF CHILDREN - Rojas de la Puente, Edward Enrique; Coronel Chugden, José Walter; Arista, Guido Ayay (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The objective of the research was to determine the influence of the interactive television program “Aula365” in the learning of children in the fourth grade of the primary level of the Educational Institution “Seminario Jesús María”, Chachapoyas-Peru; for this, the quasi-experimental research design called “design with pre and post test with non-randomized control group” has been used. The non-probabilistic sample consisted of 2 sections "B" and "C" of the fourth grade, one for the experimental group and one for the control group of 30 students each, whose average age was 9 years. The study had as an independent variable the interactive television program "Aula365" and dependent on the learning variable. The instrument used was the Barranquilla Rapid Test (BARSIT) consisting of 60 items with a single weight of 1 point each item, which determined the levels of the learning variable according to a scale of predetermined values by: very lower (0-9 ), inferior (9-18), normal (18-27), superior (27-31) and excellent (31-60). The hypothesis was contrasted by means of the statistical parameter T-Student for two independent samples, to evaluate the influence of the interactive television program "Aula365" on student learning with a 95% probability of confidence. The results in the experimental group show that the T test was statistically significant (Tc = 4.076, p <0.05), with an average of 28.4 in the pretest and 35.7 points in the post test, which evidenced an improvement in the learning of the kids; however, in the control group the T test was not statistically significant (Tc = -1,147, 0.95, p> 0.05), with an average of 20.3 in the pretest and 20.1 in the post test. Finally, it is concluded that the interactive TV program "Aula365" positively influenced, since the children achieved an excellent learning.